2011
DOI: 10.1186/1471-2377-11-30
|View full text |Cite
|
Sign up to set email alerts
|

Migraine headaches in Chronic Fatigue Syndrome (CFS): Comparison of two prospective cross-sectional studies

Abstract: BackgroundHeadaches are more frequent in Chronic Fatigue Syndrome (CFS) than healthy control (HC) subjects. The 2004 International Headache Society (IHS) criteria were used to define CFS headache phenotypes.MethodsSubjects in Cohort 1 (HC = 368; CFS = 203) completed questionnaires about many diverse symptoms by giving nominal (yes/no) answers. Cohort 2 (HC = 21; CFS = 67) had more focused evaluations. They scored symptom severities on 0 to 4 anchored ordinal scales, and had structured headache evaluations. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
2
43
1
2
Order By: Relevance
“…The association between migraine and FSSs is supported by earlier studies. [7][8][9]11,12 The current results do also confirm prior findings of an association between migraine and airway disease. 35,36 To our knowledge, neither relatively high prevalence of diagnosed exhaustion syndrome nor elevated level of burnout have previously been reported for migraine.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The association between migraine and FSSs is supported by earlier studies. [7][8][9]11,12 The current results do also confirm prior findings of an association between migraine and airway disease. 35,36 To our knowledge, neither relatively high prevalence of diagnosed exhaustion syndrome nor elevated level of burnout have previously been reported for migraine.…”
supporting
confidence: 93%
“…Thus, there is support for migraine being associated with functional somatic syndromes (FSSs; physical illnesses without an organic disease explanation and devoid of demonstrable structural lesion or established biochemical change 6 ), including fibromyalgia, 7-10 irritable bowel syndrome (IBS), 11 and chronic fatigue syndrome (CFS). 12 It has been questioned as to whether migraine should be considered a FSS. 13 According to Warren and Clauw, 14 the more interesting question may not be whether migraine is a FSS, but rather why migraine appears to be associated with these syndromes.…”
mentioning
confidence: 99%
“…The similarity between PDS and other medically unexplained conditions such as fibromyalgia [26,76], chronic fatigue syndrome [3,33,37], irritable bowel syndrome [74], post-concussion disorder [4,36], chronic headache [57], and post-traumatic stress disorder [43] has been previously noted [34]. In all these conditions, CWP occurs together with memory difficulties, fatigue, sleep disturbances and, often, depressed mood [75].…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia is very common in migraineurs with a prevalence that ranges from 16.8 to 35.6 % and, vice versa, migraine prevalence ranges from 45 to 48 % in fibromyalgia sufferers [25]. Some studies reported a bidirectional association between chronic migraine and chronic fatigue syndrome [2,26].…”
Section: Other Comorbid Disordersmentioning
confidence: 99%